1996
DOI: 10.1111/j.1399-302x.1996.tb00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Host responses induced by co‐infection with Porphyromonas gingivalis and Actinobacillus actinomycetemcomitans in a murine model

Abstract: In this study, evidence is presented that mixed infection with the periodontal pathogens Porphyromonas gingivalis and Actinobacillus actinomycetemcomitans results in a synergistic effect in their pathogenicity and in their ability to induce humoral and cellular host responses. BALB/c mice were injected subcutaneously on the back with P. gingivalis ATCC 53977, A. actinomycetemocomitans 75 or a mixture of both bacteria. Samples of blood and fluid from abscesses formed at the site of injection (first degree) or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
2
23
0
3
Order By: Relevance
“…However, the results of the present study indicated that neither P. gingivalis nor F. nucleatum induced the production of cross-reactive antibodies to B. forsythus, P. intermedia or A. actinomycetemcomitans. Chen et al [18] also showed that a subcutaneous injection of viable P. gingivalis together with A. actinomycetemcomitans resulted in the production of anti-P. gingivalis antibodies in mice injected with P. gingivalis alone with no anti-A. actinomycetemcomitans activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of the present study indicated that neither P. gingivalis nor F. nucleatum induced the production of cross-reactive antibodies to B. forsythus, P. intermedia or A. actinomycetemcomitans. Chen et al [18] also showed that a subcutaneous injection of viable P. gingivalis together with A. actinomycetemcomitans resulted in the production of anti-P. gingivalis antibodies in mice injected with P. gingivalis alone with no anti-A. actinomycetemcomitans activity.…”
Section: Discussionmentioning
confidence: 99%
“…While animal studies have demonstrated the pathogenicity of mono-infections of periodontopathogens such as P. gingivalis [13][14][15][16][17], in recent years, reports have been published on the effects of mixed microbial infections including P. gingivalis and A. actinomycetemcomitans [18], P. gingivalis and F. nucleatum [19] and P. gingivalis and B. forsythus [20] which resulted generally in increased levels of pathogenicity with a synergistic effect observed in the humoral and cellular host responses. In the human, F. nucleatum colonizes the plaque prior to P. gingivalis and high levels of F. nucleatum have been demonstrated in association with P. gingivalis as well as other bacteria associated with periodontal disease, such as B. forsythus, Prevotella intermedia and Eikenella corrodens [21].…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative evidence has indicated the significance of polymicrobial infections in which selected microorganisms interact in a synergistic or antagonistic manner, impacting on pathogenesis [7,14,15]. In the present study, we examined the ability of P.…”
Section: Discussionmentioning
confidence: 99%
“…In biofilms and biofilm-related infections, these 'effects' include increased growth, antimicrobial tolerance, virulence and persistence, and enhanced production of exopolysaccharide (EPS) [17][18][19][20][21][22][23][24][25][26][27][28]. Another classic cooperative interaction is metabolic cross-feeding, or syntrophy, where one species makes a metabolic byproduct which enhances the growth of a neighbor [29].…”
Section: • Synergismmentioning
confidence: 99%